Method and apparatus for rapid identification of column heterogeneity - DAI, Bing Tian (Institutional Knowledge at Singapore Management University, 2012)
A method and apparatus for rapid identification of column heterogeneity in databases are disclosed. For example, the method receives data associated with a column in a database. The method computes a cluster entropy for the data as a measure of data heterogeneity and then determines whether said data is heterogeneous in accordance with the cluster entropy.